PENDIMENSIAN ELEMEN STRUKTUR DITINJAU DARI DESAIN RANGKA ATAP KAYU, BAJA DAN BAJA RINGAN - Fansuri, Subaidillah; Deshariyanto, Dwi; Diana, Anita Intan Nura (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2024)
The development of technology has had a huge impact on the world of construction, especially the increasing development of construction, so the development of roof trusses cannot be separated from the role of technological developments and the increasing need for the types of roof truss materials used today. This research was carried out by collecting data obtained from literature study. Design calculations for the roof truss structure to determine the strength of the roof truss rods and a comparison of the roof truss cost budget according to 3 (three) material variations, namely wooden, steel and light steel roof trusses. The construction planning calculations are made in accordance with the Indonesian Steel Building Planning Guidelines (PPBBI), Indonesian Wood Construction Regulations (PKKI) to determine what forces and loads act on wooden, steel and light steel roof frame structures and using the SAP2000 version 14 program to design the shape. light steel roof frame. The type of wood planned for the roof frame structure is class I 8/12 wood with a load of 55.692 kg, the dimensions of the structural beam are 15 x 30 cm, the dimensions of the column structure used are 30 x 30 cm. Rp. 306,599,669.74 for the budget required, planning the WF steel roof truss structure with a profile of 300 x 150 x 6.5 x 9 with a load of 70,899 kg and beam dimensions in the plan of 15 x 30 cm, structural columns with dimensions of 40 x 40 cm. Rp. 38,964,440.84 required budget and for a light steel frame structure with a profile of 75 x 45 x 15 x 6.5 with a load of 27,837 kg and structural beams with planning dimensions of 15 x 30 cm, structural columns with dimensions of 20 x 20 cm. Rp. 245,800,149.27. budget required costs.